Strategi Marketing Public Relations Parfum Lokal dalam Membangun Brand Awareness - Azaria, Gabriella Diva; Rusdi, Farid (Prologia, 2025)
The rapid growth of the perfume industry in Indonesia, especially in the local product segment, has created intense competition among business players. Aamodini, as a new brand, had to implement effective strategies to build brand awareness. This research aims to identify the Marketing Public Relations (MPR) strategy used by Aamodini in building brand awareness. The theory used in this research is the MPR Whalen's 7 Step Strategic Planning Process, namely situation analysis, objectives, strategy, targets, messages, tactics and evaluation. The method applied is qualitative with a case study approach, where data is collected through in-depth interviews. The research results show that MPR Aamodini focuses on creating active interactions with consumers, maximizing the use of social media, collaborating with influencers, and participating in offline bazaars. These strategies can build brand awareness, starting from the initial stage where consumers are not familiar with Aamodini to reaching a significant level of recognition in the local perfume market. This research confirms the importance of a planned MPR strategy in facing competitive challenges and building brand awareness. Pesatnya pertumbuhan industri parfum di Indonesia, khususnya di segmen produk lokal, telah menciptakan persaingan yang ketat di kalangan pelaku bisnis. Aamodini, sebagai brand baru, harus menerapkan strategi yang efektif untuk membangun brand awareness. Penelitian ini bertujuan untuk mengidentifikasi strategi Marketing Public Relations (MPR) yang digunakan Aamodini dalam membangun brand awareness. Teori yang digunakan dalam penelitian ini adalah Tahapan MPR Whalen’s 7 Step Strategic Planning Process, yakni analisis situasi, objektif, strategi, sasaran, pesan, taktik, dan evaluasi. Metode yang diterapkan adalah kualitatif dengan pendekatan studi kasus, di mana data dikumpulkan melalui wawancara mendalam. Hasil penelitian menunjukkan bahwa MPR Aamodini berfokus pada menciptakan interaksi aktif dengan konsumen, memaksimalkan penggunaan media sosial, berkolaborasi dengan influencer, dan berpartisipasi dalam bazaar offline. Strategi-strategi ini dapat membangun kesadaran merek, mulai dari tahap awal di mana konsumen tidak mengenal Aamodini hingga mencapai tingkat pengenalan yang signifikan di pasar parfum lokal. Penelitian ini menegaskan pentingnya strategi MPR yang terencana dalam menghadapi tantangan kompetisi dan membangun brand awareness.